Experimental study on the behavior of lightweight concrete sandwich panels under axial compression - Joseph, J. Daniel Ronald; Prabakar, J.; Alagusundaramoorthy, P. (Journal of Structural Engineering, 2024)
In this paper, results of experimental studies carried out to understand the behavior of prototype lightweight concrete sandwich panels under axial compression are presented and discussed. Four different configurations of the panels with different panel thickness and size of weld mesh used as reinforcement in concrete wythes of 3m height were tested under axial compression till failure. Self-compacting concrete was used for casting concrete wythes and expanded polystyrene (EPS) was used as insulation material. Wire mesh with two different mesh sizes such as 50-mm and 100-mm were considered. Truss-type shear connectors made of wires were used to achieve composite action. Experimental study indicates that stiffening concrete beams near loading and the support regions improved the composite action of the panels and precluded panel failure due to local crushing of concrete wythes. Also, shear connectors were found to be effective in ensuring composite action until failure of the panels. The panels with relatively less thickness failed by buckling at a cross section away from the loading region whereas the panel with higher thickness failed by buckling near the loading region. It is noted that even though mesh size and EPS thickness were varied, the ultimate load of the panels (with stiffening beam) tested are comparable due to same area of concrete wythes.